Effects of Ability to Assess Fraud Risk, Fraud Risk Level and Personality Factors on the Ability to Detect the Likelihood of Fraud - Jaffar, Nahariah (2008)
The Malaysian Approved Standards on Auditing, A1 700 on "The Auditor's Report on Financial Statements" (MIA, 1997) states that the responsibility of the auditor is to provide assurance that the financial statements are free from material misstatements. Misstatement may be due to error or fraud. Error is unintentional misstatement while fraud is intentional misstatement. Fraud, which can be divided into two types i.e. fraudulent financial reporting and misappropriation of assets, may both cause materially misleading financial statements (Elliot & Willingham, 1980). In Malaysia, although standards and guidelines have been issued, yet fraudulent financial reporting still occurs in this country as reported by the KPMG Malaysia's (2003) survey. Although the issue of fraud may not be well documented in Malaysia, this issue cannot be taken for granted since what happens in other countries, for instance in the US, may also happen elsewhere. Even though guidance has already been provided by the Malaysian standards, KPMG Malaysia's (2003) survey reports that external auditors discover only 4% of fraud incidences in Malaysian companies. Due to this, the public may question why external auditors are not able to detect fraud during the conduct of the annual audit. Therefore, it is important to know the ability of the external auditor to detect fraud because fraudulent financial reporting is false representation to society. The A1 240 on "Fraud and Error" (MIA, 1997) requires the external auditor to appropriately assess fraud risk during the planning of the audit work so that helshe can provide reasonable assurance that any material misstatement in the financial statements has been detected. The ability of the external auditor to detect the likelihood of fraud may be influenced by hislher ability to appropriately assess the fraud risk. Meanwhile, the concept of fraud risk underlying the audit risk model would be fundamental in influencing the external auditors' ability to detect the likelihood of fraud. In addition, literature has shown that personality moderates the relationship between a construct and job performance. Therefore, the objective of the present study is to examine the effect of the external auditors' ability to assess fraud risk on their ability to detect the likelihood of fraud. In addition, the present study examines the moderating effects of fraud risk level and personality factors on the relationship between the external auditors' ability to assess fraud risk and their ability to detect the likelihood of fraud.